Traffic Engineering Management of Cikarang Wholesale Center, Cikarang Terminal, and Jababeka Area - Rozi, M. Hillal Fahrul; Susilo, Budi Hartanto; Yuwono, Bambang Endro; Maha, Indra; Ma'soem, Dadang Mohamad (Universitas Ibn Khaldun Bogor, 2025)
Bekasi Regency is the second highest in the number of motorized vehicles for motorbikes and first for cars. During peak hours at certain sections and intersections, especially in the SGC area, Cikarang Terminal and Jababeka area, there are traffic problems ranging from side obstacles, public transport dropping/picking up passengers incorrectly, and so on. The aim of this research is to outline the performance of existing sections and intersections in the SGC area, Cikarang Terminal and Jababeka area as well as identify existing traffic problems and how to handle them. The methods used are Four step model, section performance analysis, intersection performance analysis, Forecasting, model validation and using PTV Vissim. The research results show that there are 3 problematic road segments with a high level of service, including Jl. Fatahillah 2, Jl. Raya Industri, Jl. Captain Sumantri with a VC Ratio of 0.75, 0.85, and 0.94 respectively and there are 6 of the 9 intersections that have problems, namely the Brigief Dormitory intersection, the terminal intersection, the Yos Sudarso-Kp.Sumantri intersection, the Arief Rahman Hakim- Jl .Industry intersection, Pasir Gombong intersection and SGC intersection. Changes resulting from traffic management and engineering are not very significant every 5 years because many drivers will switch to the road section with the lowest VCR.